Cost-effectiveness of antihypertensive treatment in Malaysia - Al-Efan, Qais Muhammad Ahmad; M. Ibrahim, M. Izham; Abdul Razak, Tariq; Ayob, Azizi (Penerbit USM, 2009)
Hypertension is a prevalent chronic disease, which is strongly related to the development of cerebrovascular and cardiovascular diseases. The prevalence of hypertension in Malaysia in subjects aged 15 years and above was estimated to be 27.8%. Cost-effectiveness analysis (CEA) compares treatment options with different effectiveness and safety profiles. The utilisation of antihypertensive drugs has raised some concerns about the balance between its costs and benefits. This study was conducted to describe the healthcare costs for hypertensive subjects and to examine the cost-effectiveness of different classes of antihypertensive drugs used in Malaysia. Retrospective and prospective data analysis of a cohort of uncomplicated hypertensive patients was conducted to determine ambulatory health care costs among hypertensive patients groups. The total direct and indirect costs of controlled and uncontrolled blood pressure (BP) were described. The health care costs ($) / clinical outcome (AC/E ratio) was calculated. Mean total direct costs per patient per month was higher in uncontrolled blood pressure groups compared to the controlled blood pressure groups. The cost-effectiveness relationship was more favourable for diuretics (1.9), angiotensin converting enzyme inhibitors (ACEIs) (2.0), prazosin (2.4) and beta blockers (2.5), more than the diuretics and beta blockers combination theraphy (3.0), calcium channel blockers (CCBs) (3.4) and other combinations (6.1). Antihypertensive drugs used to treat hypertensive patients were different in their cost-effectiveness ratios. Such results will allow health care professionals and/or decision makers to make better decisions on how to select treatment options for hypertensive patients in Malaysia and how to distribute and allocate scarce health care resources. Pharmacoeconomic evaluations can help in making difficult choices rationally and allocate scarce resources efficiently.